2007
DOI: 10.1186/1744-9081-3-64
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydroisoquinoline derivatives: a new perspective on monoaminergic dysfunction in children with ADHD?

Abstract: BackgroundThe dopamine-derived tetrahydroisoquinolines (TIQ) synthesized endogeneously from aldehydes and catecholamines have shown to modulate neurotransmission, central metabolism and motor activity. Converging evidence has implicated abnormalities of the dopamine metabolism to the pathophysiology of Attention-Deficit/Hyperactivity Disorder (ADHD). Therefore, four TIQ derivatives involved in central dopamine metabolism (salsolinol, N-methyl-salsolinol, norsalsolinol, N-methyl-norsalsolinol) have been analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…However, N-methyltransferases enzymes can act salsolinol it to create N-methyl-salsolinol, which has been demonstrated to be neurotoxic to SH-SY5Y neuroblastoma cells [211]. By a similar pathway, dopamine and formaldehyde can react to yield the putative toxicants norsalolinol and N-methyl-norsalsolinol [212]. Norsalsolinol has been shown in vitro to be transport substrate for plasmalemmal and vesicular transporters, suggesting a potential for a protective effect of VMAT2 similar to that for MPP + [213,214].…”
Section: Vesicular Transport and Neurotransmitter Toxicitymentioning
confidence: 98%
See 1 more Smart Citation
“…However, N-methyltransferases enzymes can act salsolinol it to create N-methyl-salsolinol, which has been demonstrated to be neurotoxic to SH-SY5Y neuroblastoma cells [211]. By a similar pathway, dopamine and formaldehyde can react to yield the putative toxicants norsalolinol and N-methyl-norsalsolinol [212]. Norsalsolinol has been shown in vitro to be transport substrate for plasmalemmal and vesicular transporters, suggesting a potential for a protective effect of VMAT2 similar to that for MPP + [213,214].…”
Section: Vesicular Transport and Neurotransmitter Toxicitymentioning
confidence: 98%
“…Norsalsolinol has been shown in vitro to be transport substrate for plasmalemmal and vesicular transporters, suggesting a potential for a protective effect of VMAT2 similar to that for MPP + [213,214]. While not constituting proven disease mechanisms, these TIQs are hypothesized to impact the etiology of several disorders including addiction, attentiondeficit hyperactivity disorder and Parkinson's disease, possibly by interfering with dopamine production, storage, or degradation [212,[215][216][217][218][219].…”
Section: Vesicular Transport and Neurotransmitter Toxicitymentioning
confidence: 98%
“…There is evidence that these derivatives are involved in central dopamine metabolism (Briggs et al 2013) and in the modulation of dopaminergic neurotransmission (Xie et al 2012). In a previous study, we found higher concentrations of all these dopamine-derived metabolites in urine of ADHD patients, a condition also discussed to be associated with a disturbed dopamine neurotransmission (Roessner et al 2007).…”
Section: Introductionmentioning
confidence: 66%
“…ADHD has already been described before as a condition associated with elevated TIQ levels (Roessner et al 2007 ). This assumption is strengthened by the fact that the original publication on elevated TIQ levels in ADHD patients (which recruited its patients in the same centers) exhibited the most pronounced elevation for NSAL as well.…”
Section: Discussionmentioning
confidence: 85%
“…Numerous methodologies have been reported for the syntheses of THIQ analogs . In particular, THIQs substituted at the C1 and N positions display various biological activities, such as antitumor, anti‐HIV, antibacterial, and neuroprotective . For instance, solifenacin is an approved drug as a selective muscarinic M3 receptor antagonist for the treatment of overactive bladder (Figure ) .…”
Section: Introductionmentioning
confidence: 99%